LITERACY FROM A LITERACY PERSPECTIVE: CHALLENGES FOR THE NEWLY GRADUATED TEACHER - Dias Dos Santos, Deusiane (Revista Gênero e Interdisciplinaridade, 2024)
Historically, in our educational context, the work of teachers, especially recent graduates, has faced several challenges, especially when it comes to literacy in the initial grades of elementary school. A teacher who begins his career in literacy usually faces large classes and needs to deal with students who have different knowledge and experiences. Many students often have difficulties acquiring reading and writing skills and need interventions suited to their real needs. This article aims to present reflections/discussions/analyses about literacy for teaching reading in early grades. In terms of challenges, we observed the following results: the weakening of initial training, which ends up distancing theory from practice; classrooms with many students; internships carried out with gaps in supervision; curricula with more emphasis on theories than on literacy practices/methodologies; the lack of planning, or even a political pedagogical project, that guides the newly graduated literacy teacher in their work; in addition to the discontinuity of continuing education policies.